1989
DOI: 10.1212/wnl.39.5.713
|View full text |Cite
|
Sign up to set email alerts
|

Posthypoxic treatment with MK‐801 reduces hypoxic‐ischemic damage in the neonatal rat

Abstract: We evaluated the neuroprotective effect of MK-801, a noncompetitive, selective N-methyl-D-aspartate receptor antagonist, in a neonatal hypoxic-ischemic animal model. Seven-day-old rats underwent bilateral ligation of the carotid arteries followed by exposure to an 8% oxygen atmosphere for 1 hr. We sacrificed the animals 72 hrs later and assessed the hypoxic-ischemic brain damage histologically. MK-801 (10 mg/kg), administered IP 0.5 hr before the hypoxia, completely prevented hypoxic-ischemic infarction in cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
3

Year Published

1990
1990
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(47 citation statements)
references
References 0 publications
0
44
0
3
Order By: Relevance
“…Effective levels of NOARG would not be reached because the peritoneal vascular beds are vasoconstricted and absorption is slow. The lack of posthypoxic effect of the NO synthase inhibitor is not in accord with the neuroprotective effect of posthypoxic treatment with the NMDA receptor antagonist, MK-801, in another neonatal rat model of hypoxic-ischemic brain damage (4).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Effective levels of NOARG would not be reached because the peritoneal vascular beds are vasoconstricted and absorption is slow. The lack of posthypoxic effect of the NO synthase inhibitor is not in accord with the neuroprotective effect of posthypoxic treatment with the NMDA receptor antagonist, MK-801, in another neonatal rat model of hypoxic-ischemic brain damage (4).…”
Section: Discussionmentioning
confidence: 87%
“…In the prehypoxic damage in immature rats is identical in appearance and time treatment group (group 1, n = 12 pairs), 2 mdkg of NOARG course to the cfiotoxic reaction to NMDA (3). MK-801 [(+)-5-(Sigma Chemical CO., St. Louis, MO) was administered intramethyl-10,11-dihydro-5H-dibenzo[a1d]cyclohepten-5, 10-imine peritoneally 1.5 h before the h~x i c insult-The reason why we maleate], a noncompetitive NMDA antagonist, protects against chose the dose of 2 mdkg is that, in preliminary experiments, h xic-ischemic brain damage in neonatal rats (4 group (group 2, n = 12 pairs), 2 mg/kg of NOARG was given immediately after the cessation of hypoxia. Each experimental animal received NOARG dissolved in normal saline (5 mllkg), and its paired littermate was administered the same volume of normal saline.…”
Section: Abbreviationsmentioning
confidence: 99%
“…However, most of the H-I-induced brain injury in P7 rats can be blocked by pretreatment with the NMDAR antagonist, MK801 (13). This result suggests that glutamate toxicity in the setting of neonatal H-I initiates both necrotic and apoptotic cell-death pathways (13,31). Further, it has been shown that necrosis is the cell-death pathway that is used immediately after the H-I in neonates and after glutamate challenges in cortical cultures (10,43,46).…”
Section: Discussionmentioning
confidence: 98%
“…H-I-induced brain injury in P7 rats can be blocked by pretreatment with the NMDA receptor (NMDAR) antagonist, MK801 (13,31). This finding suggests that glutamate-mediated toxicity via NMDARs in the setting of neonatal H-I initiates cell death with both necrotic and apoptotic features.…”
Section: Cytnmnat1 Protects Neuronal Processes and Cell Bodies Againstmentioning
confidence: 98%
“…11). Further evidence for the "excitotoxic" theory is provided by experiments that show that antagonists to NMDA can prevent cerebral ischemic injury (12)(13)(14).…”
mentioning
confidence: 99%